2017
DOI: 10.1039/c7cc02394d
|View full text |Cite
|
Sign up to set email alerts
|

Crystallographic analyses of isoquinoline complexes reveal a new mode of metallo-β-lactamase inhibition

Abstract: Crystallographic analyses of the VIM-5 metallo-β-lactamase (MBL) with isoquinoline inhibitors reveal non zinc ion binding modes. Comparison with other MBL-inhibitor structures directed addition of a zinc-binding thiol enabling identification of potent B1 MBL inhibitors. The inhibitors potentiate meropenem activity against clinical isolates harboring MBLs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 28 publications
4
19
0
Order By: Relevance
“…126 In addition, captopril 40 an FDA-approved drug used for the treatment of hypertension, has also received some attention for its ability to inhibit NDM-1 (IC 50 = 7.9 μM). 127 Building upon these findings efforts have been made to replace the prolyl residue of captopril with various other functional groups, [127][128][129][130] as well as modification of the thiolated acyl residue, and/or ring size. 129,131 Brem and coworkers also found the MBL inhibition of D-captopril to be superior to that of its other stereoisomers when evaluated against BCII, IMP-1, VIM-2, NDM-1, and SPM-1.…”
Section: Recent Advances In the Development Of Mbl Inhibitorsmentioning
confidence: 99%
“…126 In addition, captopril 40 an FDA-approved drug used for the treatment of hypertension, has also received some attention for its ability to inhibit NDM-1 (IC 50 = 7.9 μM). 127 Building upon these findings efforts have been made to replace the prolyl residue of captopril with various other functional groups, [127][128][129][130] as well as modification of the thiolated acyl residue, and/or ring size. 129,131 Brem and coworkers also found the MBL inhibition of D-captopril to be superior to that of its other stereoisomers when evaluated against BCII, IMP-1, VIM-2, NDM-1, and SPM-1.…”
Section: Recent Advances In the Development Of Mbl Inhibitorsmentioning
confidence: 99%
“…1). 15,17,19 And the carbonyl group makes hydrogen-bonding interactions with catalytically important residue Asn233 on the L3 loop. In addition, the phenyl group forms face-to-face p-p interactions with Tyr67 on the L1 loop.…”
Section: Crystallographic Analysismentioning
confidence: 99%
“…13 So far, various types of MBL inhibitors have been reported, such as thiol-containing compounds, cyclic boronates, succinic acids, carboxylates and others. [14][15][16][17][18][19][20] Most MBL inhibitors work via active-site metal chelation manner, and more importantly, the broad-spectrum MBL inhibitors have metal chelation and anchor residue binding features. 14 Despite progress has been made, there is still a need to develop new broad-spectrum MBL inhibitors to provide candidates for the development of clinically useful MBL inhibitors.…”
Section: Introductionmentioning
confidence: 99%
“…Compound 4, an inhibitor used in clinical practice, also showedmoderate anti-NDM-1 activity(IC 50 =10.4µM) and low toxicity [38]. Crystallographic analyses ofthe VIM-5 metallo-β-lactamase (MBL) with isoquinoline inhibitors revealed non-zinc ion binding modes [39]. Compared with other MBL-inhibitor structures with a zinc-binding thiol,thecompounds potentiatedmeropenem activity againstclinical isolates harboring MBLs.Yusof et al [40] recently revealed that the potency of these inhibitors could be improved by shortening the length of the mercaptoalkanoyl sidechain, as exemplified by com-pounds5(K i = 2.3 ± 1.5 µM) and 6 (K i = 2.9 ± 0.9 µM).…”
Section: Thiol Derivativesmentioning
confidence: 99%